Unlocking Land Values for Urban Infrastructure Finance : International Experience--Considerations for Indian Policy - Peterson, George E. (World Bank, Washington, DC, 2014)
Despite strong economic growth, investment in basic urban infrastructure -- water supply, wastewater removal and treatment, roads, and other capital-intensive systems -- has failed to keep pace with urban growth, leaving a critical urban infrastructure deficit. At the same time, urban lands in these many developing countries are among the most expensive in the world. Much of this land is owned by public authorities. Significant parts of it lie vacant, unused for public service provision or inappropriate for conversion to higher-valued economic activity. A composite public-sector balance sheet for India's urban areas would show an asset mix strong on public-sector landholdings but weak on infrastructure. This raises the following questions: Can some excess public-sector land be exchanged for infrastructure, in a manner that is politically acceptable and economically efficient? Can public land sales be a realistic source of finance for critically needed urban infrastructure investment? This paper considers the policy context that has shaped different land-disposal and earmarking initiatives, provides details about the actual workings of institutions, and examines international experience in infrastructure investment. This study contributes to the consultative process underway in India to consider strategies to unlock public land values to help finance urban infrastructure investment.